ANALYST OF THE BALANCE BETWEEN SHARIA PRINCIPLES AND THE PERFORMANCE OF SHARIA MUTUAL FUNDS IN INDONESIA: A PERSPECTIVE OF SHARIA ECONOMIC LAW - Lisda Dwi Andini; Muhammad Alif Najiyya (Walisongo Journal of Sharia Economic Law, 2025)
This study aims to analyze the balance between the application of sharia principles and the performance of sharia mutual funds in Indonesia from the perspective of sharia economic law. In the context of the Islamic capital market, Islamic mutual funds are not only required to achieve competitive financial performance, but must also uphold sharia principles such as the halalness of the portfolio, the involvement of the Sharia Supervisory Board, and the fulfillment of the principles of fairness and transparency. This study uses a qualitative approach with a normative-empirical method. Data was obtained through the study of documents, regulations, and interviews with capital market practitioners and relevant authorities. The results of the study show that although most sharia mutual funds have followed the formal sharia provisions set by DSN-MUI and OJK, there are dynamics in management practices that show a tension between profitability orientation and commitment to sharia principles.